Pengaruh Risk-Taking dan Free Cash Flow Terhadap Kebijakan Dividen - Indriani, Dea; Rahman, Fauziah; Putri Sirait, Devi Ayu; Dewi, Sucitra (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2025)
This study aims to analyze the impact of risk-taking and free cash flow on dividend policy. The novelty of this study lies in the quantitative analysis of the influence of risk-taking and free cash flow on dividend policy in construction and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023 using multiple linear regression. This study simultaneously combines internal variables and uses the most recent data, differing from previous studies that were more limited to specific sectors or used different methodologies, thus making the results more valid and relevant for strategic decision-making. This study adopts a causal quantitative approach to examine the influence of risk-taking and free cash flow on dividend policy by implementing classical assumption testing, a prerequisite for multiple linear regression analysis, including assumption testing and hypothesis testing, to ensure the stability and validity of the analytical model. Dividend policy in commercial banks listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023 was influenced by risk-taking and free cash flow simultaneously. This study is limited to companies in the construction and real estate sectors listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. Therefore, the research results cannot be generalized to other industrial sectors or to companies not listed on the IDX. Furthermore, only two independent variables were analyzed: risk-taking and free cash flow. Therefore, other variables that could also influence capital structure are not described in this model. This finding has implications, particularly for company management. High risk-taking can make companies more cautious in distributing dividends because increased business risks require profit retention as a capital buffer. High free cash flow provides companies with the financial capacity to pay dividends regularly and stably without disrupting working capital and investment needs. Therefore, the combination of these two factors reflects a balance between a company's cash flow capacity and risk management strategy in determining dividend policy.